Inspiration from Daughterto the Love Power of Father Concept in 3D mixed media art - Veeranoi, Isara (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
This article is an educational and creative study: Inspiration from Daughter to the Love Power of Father Concept in 3D mixed media art with the following key points: 1. The origin and importance of inspiration such as the relationship, love story and about the father's role in relation to the child. 2. Analysis of inspiration to create ideas. 3. Creation of 3D mixed media art such as creation, process of creating, design, material selection and creation methods. 4. Presentation of the completed 3D mixed media art.